Efficacy of hyaluronidaze in reducing vitreous opacites – preliminary report - Puchalska-Niedbał, Lidia; Millo, B (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
The aim of the work: the assesment of hyaluronidase as reducer of floaters in vitreus body. We present one patient with the floaters in vitreus body treated by subconjunctival injection with hyaluronidase. Research work was carried out on a rabbit, which had been given 10 subconjunctival injections of hyaluronidaze. After treatment we noted subjective and local improvement. By using biochemical tests we proved, that subconjunctival hyaluronidaze application is a good way, to obtain an effect in the vitreous.